PENGARUH MODAL KERJA TERHADAP LIKUIDITAS PADA KEGIATAN USAHA PERDAGANGAN - Sofiah Nur Iradawati (BALANCE: Economic, Business, Management and Accounting Journal, 2011)
Working capital is one of important factors in conjunction with the company's day-to-day activities, as well as indicate the level of security (margin of safety) for the creditors, especially short-term creditors. The importance of working capital for the company as proposed by S. Munawir (1997; 116) as follows: "The availability of working capital should be sufficient in number in the sense to be able to pay for the expenses or the company's day-to-day operations, because with sufficient working capital will be profitable for the company, as well as allow the company to operate economically or efficient, and the company is not experiencing financial difficulties. Working capital in an operation or spinning in the company, as long as the business is concerned in the state. Working capital turnover period (Working Capital Turn Over Period) begins at a time when invested in the components of working capital to return to the time when the cash, the shorter the faster turnover means higher turnover or turnover rate (Turn over rate is). Bambang Riyanto (1999; 54) in his book "Fundamentals of corporate expenditures" said: "How long period working capital turnover is dependent on how long the turnaround in each component of working capital and also said that the working capital turnover for merchandise is faster than the turnover period keija for goods that undergo the process of production ". To finance working capital can come from short-term debt, long term debt and equity capital. How to finance current assets this have any impact on the liquidity and profitability of the company. From the view of liquidity, current assets should dibelanjai with long-term debt and equity capital for the long life of the credit term is taken to mean the company the opportunity to obtain cash inflows so that the company can repay its debts. If the shorter the life of the credit means that the shorter the company the opportunity to obtain cash inflows, so the more likely it can not pay back its debts maturing. Being from the profitability point of view, it is precisely the use of long-term debt to finance assets will increase costs, because of the period in which the loan is not used for the company but had to pay interest. Another case when companies use short-term debt as short-term debt can be paid back over a period in which the debt is not necessary. So it is clear that how current assets will have a significant dibelanjai on liquidity and profitabitas company. Basically the capital expenditure policy can be divided into three, namely:1) conservative spending policy: Here companies finance most of its short term financial needs with long-term spending. It is intended as a precaution in case of deviation company's net cash inflows are not having trouble paying their obligations in cash. If it happens as expected cash flows, the company will pay interest for the period in which the funds are not actually needed. 2) Aggressive Spending Policy: The policy is all fixed asset purchases financed by the company's long-term capital, but most of the permanent current assets financed with short-term credit. As a result, the company should be able to renew short-term debt that is embedded in a permanent asset, and this involves the risk borne by the company, and 3) Moderate Spending Policy: In this policy permanent financing than with the nature of the assets, the company tried to bring the maturity between assets and liabilities and their rigorous. If total assets increased permanent, it will be financed with equity, long term debt and a permanent part of current liabilities,Â Â Kata Kunci: Aktiva, Pembelanjaan, Likuiditas, Profitailitas.